Dravet Syndrome as an Example of Precision Medicine in Epilepsy. Issue 1 (January 2023) - Sullivan, Joseph; Wirrell, Elaine C.
Dravet syndrome (DS) is a drug-resistant, early-onset, developmental and epileptic encephalopathy where there have been many recently approved therapies with many more in development. With the availability of more syndrome specific treatment options coupled with an earlier diagnosis, DS is well-positioned to be an example of how a precise syndromic diagnosis can guide treatment choices and improve overall outcomes and also allow for the development of potential disease modifying therapies to address more than just seizures. In this review we summarize the current state of DS approved therapies and those that are in various stages of development.